Solve tan 10 - tan 50 +tan 70 with trigonometry.
1 answer:
Below is the solution, I hope it helps.
<span>i) tan(70) - tan(50) = tan(60 + 10) - tan(60 - 10)
= {tan(60) + tan(10)}/{1 - tan(60)*tan(10)} - {tan(60) - tan(10)}/{1 + tan(10)*tan(60)}
ii) Taking LCM & simplifying with applying tan(60) = √3, the above simplifies to:
= 8*tan(10)/{1 - 3*tan²(10)}
iii) So tan(70) - tan(50) + tan(10) = 8*tan(10)/{1 - 3*tan²(10)} + tan(10)
= [8*tan(10) + tan(10) - 3*tan³(10)]/{1 - 3*tan²(10)}
= [9*tan(10) - 3*tan³(10)]/{1 - 3*tan²(10)}
= 3 [3*tan(10) - tan³(10)]/{1 - 3*tan²(10)}
= 3*tan(30) = 3*(1/√3) = √3 [Proved]
[Since tan(3A) = {3*tan(A) - tan³(A)}/{1 - 3*tan²(A)},
{3*tan(10) - tan³(10)}/{1 - 3*tan²(10)} = tan(3*10) = tan(30)]</span>
You might be interested in
Answer:
B.) 132
Step-by-step explanation:
Got it correct
-2(3x-4)=4(5x-11)
-6x+8=20x-44
8+44=26x
26x=52
x=52/26
your answer will be x=2
Answer:
imvnuifdv
Step-by-step explanation:
Answer:
70.91 x 10 = 709.1
70.91 x 100 = 7,091
70.91 x 1000 = 70,910
Answer:
<em>1690</em>
Step-by-step explanation:
V = LWH
V = 13 * 10 * 13
V = 1690